Regorafenib Alteration of the BCL-xL/MCL-1 Ratio Provides a Therapeutic Opportunity for BH3-Mimetics in Hepatocellular Carcinoma Models - Cucarull, Blanca (Cancers (Basel), 2020)
Background: The multikinase inhibitor regorafenib, approved as second-line treatment for hepatocellular carcinoma (HCC) after sorafenib failure, may induce mitochondrial damage. BH3-mimetics, inhibitors of specific BCL-2 proteins, are valuable drugs in cancer therapy to amplify mitochondrial-dependent cell death. Methods: In in vitro and in vivo HCC models, we tested regorafenib’s effect on the BCL-2 network and the efficacy of BH3-mimetics on HCC treatment. Results: In hepatoma cell lines and Hep3B liver spheroids, regorafenib cytotoxicity was potentiated by BCL-xL siRNA transfection or pharmacological inhibition (A-1331852), while BCL-2 antagonism had no effect. Mitochondrial outer membrane permeabilization, cytochrome c release, and caspase-3 activation mediated A-1331852/regorafenib-induced cell death. In a patient-derived xenograft (PDX) HCC model, BCL-xL inhibition stimulated regorafenib activity, drastically decreasing tumor growth. Moreover, regorafenib-resistant HepG2 cells displayed increased BCL-xL and reduced MCL-1 expression, while A-1331852 reinstated regorafenib efficacy in vitro and in a xenograft mouse model. Interestingly, BCL-xL levels, associated with poor prognosis in liver and colorectal cancer, and the BCL-xL/MCL-1 ratio were detected as being increased in HCC patients. Conclusion: Regorafenib primes tumor cells to BH3-mimetic-induced cell death, allowing BCL-xL inhibition with A-1331852 or other strategies based on BCL-xL degradation to enhance regorafenib efficacy, offering a novel approach for HCC treatment, particularly for tumors with an elevated BCL-xL/MCL-1 ratio.